CAPSULAR GENOTYPING OF Klebsiella pneumoniae ISOLATED FROM CLINICAL SAMPLES AT SANGLAH GENERAL HOSPITAL IN 2013 - I Made Sutha Saskara; Ni Nengah Dwi Fatmawati; Ni Nyoman Sri Budayanti; Wahyu Hidayati (Institute for Research and Community Services Udayana University, 2017)
Klebsiella pneumoniae, one of hospital associated infections agents, become more prevalence in worldwide. It is an opportunistic pathogen that can cause wide spectrum of diseases such as pneumonia and sepsis. Capability of this bacterium in causing diseases is influenced by its virulence factors. Capsule (K) is considered as the major virulence factor responsible in avoiding first defense mechanism of host cells. Almost no study about molecular characterization of capsule is reported in Bali; therefore, this study is aimed to determine the capsular genotype of K. pneumoniae isolated from clinical specimens at Sanglah General Hospital. Samples were collected between January until Desember 2013 in Sanglah General Hospital at Clinical Microbiology Laboratory. Total of 56 samples were examined taken from blood, urine, pus, sputum, and other sources. All K. pneumoniae DNA were then subjected to PCR using specific primer pairs against K1, K2 and K5. The results showed that from 56 K. pneumoniae clinical isolates only 12 (21.4%) were PCR positive, and all (100%) of them were positive for K2 capsule gene. Ten (83.3) of them were from blood, 1 (8.3%) from sputum, and 1 (8.3%) from other specimens. Finding of K2 capsule gene in most K. pneumoniae clinical isolates at Clinical Microbiology Laboratory in Sanglah General Hospital might figure out the relationship of capsular type with severity of diseases. However, further study of capsule in Bali with higher isolates number will help in understanding of pathogenicity of K2 capsule in order to treat the infections itself.